PESAN DAKWAH DALAM QOSIDAH MUKTAMAR KE-34 NU KARYA DR. (H.C.) KH. AFIFUDDIN MUHAJIR - Harif Yurman Syahfajri; Wisri; M.Syakur (Maddah : Jurnal Komunikasi dan Konseling Islam, 2024)
The Qosidah of the 34th Congress is a syi'iran written by DR. (H.C) KH. Afifudin Muhajir's intention was none other than Mahabbah's love for Nahdlatul Ulama, with the hope that it would be a means of gaining the approval of Al lah SWT. Therefore, the author's aim in conducting this research is to describe the da'wah message contained in the muktamar qosidah by DR. (H.C) KH. Afifuddin Muhajir. The research method used in this research is library research or what is usually called the Hermeneutics method. This method focuses on the activity of interpreting or meaning the text contained in the research object being studied. The conclusion and results of this research are that the da'wah messages studied by researchers are that there are three categories of da'wah messages, namely creed messages, sharia messages and moral messages. Of the three messages that researchers can express in the qosidah congress, there are three types of aqidah messages, namely faith in Allah, Allah's Messen ger and faith in the qodlo and qadar of Allah SWT. Meanwhile, there are two sharia messages contained in the qosidah, namely the sharia message in the form of worship, namely prayer and the sharia message in the form of deliberation. Finally, the moral mes sage contained in the qosidah is morals towards Allah, the Messenger of Allah and morals towards humans which are divided into three, namely morals towards oneself, towards family and towards other people.